2015
DOI: 10.3844/jssp.2015.363.380
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Children and Young People’s Participation in Policy Making in Ghana

Abstract: This research examined the barriers to young people's participation as strategic stakeholders in the formulation of public policy, using the formulation of Ghana's youth policy as a case study. The aim was to gain knowledge about the processes that facilitate or hinder young people's participation in the policy process at national level. The study involved the use of semi-structured interviews and focus group discussions with 20 stakeholders in the policy process. Findings showed discrepancy in the attitudes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Yet recent reports on the KG sector have concluded that the curriculum is rarely implemented, and that quality is low across the country (GES, 2012;UNESCO, 2006). Pedagogical practices observed in several studies in Ghana are highly teacher-directed and considered to be oppressive of young children (Adu-Gyamfi, 2014;Akyeampong, 2017), with children viewed as "receptacles in need of control" (Agbenyega, 2017, p. 682). Thus, despite the national curriculum being play-based and child-centered, it is rarely implemented as intended (Ghana Education Service, 2012).…”
Section: Kindergarten Education In Ghanamentioning
confidence: 99%
“…Yet recent reports on the KG sector have concluded that the curriculum is rarely implemented, and that quality is low across the country (GES, 2012;UNESCO, 2006). Pedagogical practices observed in several studies in Ghana are highly teacher-directed and considered to be oppressive of young children (Adu-Gyamfi, 2014;Akyeampong, 2017), with children viewed as "receptacles in need of control" (Agbenyega, 2017, p. 682). Thus, despite the national curriculum being play-based and child-centered, it is rarely implemented as intended (Ghana Education Service, 2012).…”
Section: Kindergarten Education In Ghanamentioning
confidence: 99%
“…However, there are barriers to ensuring youth participation. According to Adu Gyamfi (2015), politicians perceptions of youths maturity level and lack of life experience contribute to the failure to include youths in the policy-making process. Furthermore, many studies on youth participation have discovered that youth are perceived as incompetent, passive, immature, incomplete, and highly fragile subjects whose participation is unreliable and vulnerable to adult suggestions (Mishna et al, 2004;Farrell, 2005;Laenen, 2009;Mason and Hood, 2011;Fisher et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are barriers to ensuring youth participation. According to Adu Gyamfi (2015), politicians perceptions of youths maturity level and lack of life experience contribute to the failure to include youths in the policy-making process. Furthermore, many studies on youth participation have discovered that youth are perceived as incompetent, passive, immature, incomplete, and highly fragile subjects whose participation is unreliable and vulnerable to adult suggestions (Mishna et al, 2004;Farrell, 2005;Laenen, 2009;Mason and Hood, 2011;Fisher et al, 2013).…”
Section: Introductionmentioning
confidence: 99%